EFEKTIVITAS DIGITALITASI INFORMASI AKUNTANSI TERHADAP KINERJA KEUANGAN DI USAHA VALUTA ASING - Kadlina, Kadlina; Munandar, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This article intends to know Effectiveness of Digitalization an Accounting Information of Financial Performance in foreign exchange business. There are 5 system and website that used by company, for process the data until finish the report (Accurate), for attandance purpose and payroll system (Greatday), for daily transaction and profit target achievement (operating project system) with customer database, include 2 public service websites managed by the Government: (DJP online for tax), Bank Indonesia (Laporan Kegiatan Usaha/LKU). In this research, used qualitative method analysis by data before and after using Accounting Information system in company.